Post-recession business growth:impact on ROE in the long and short term - Vladislav Spitsin; Marina Ryzhkova; Lubov Spitsina; Victoria Leonova (Retos: Revista de Ciencias de la Administración y Economía)
At the beginning of the current century, the world economy experienced several crisis events that negatively influenced business performance. Many businesses have experienced long periods of declining sales. This paper continues the series of scientific works on the study of restarting growth, i.e., the growth of companies after a long period of stagnation or falling sales. The paper contributes to the world literature by analyzing the impact of different types of restarting growth on firm performance (firm’s return on equity – ROE). The panel data includes 7528 observations (1882 firms * 4 years). Regression models with fixed effects are used for data analysis. The study revealed a positive impact of long-term growth on ROE, but it did not confirm the impact of short-term growth on ROE. The maximum benefits accrue to young companies with long-term fast sales growth. Empirical studies provide varying results on the impact of growth on firm profitability. Our approach reconciles these contradictions and shows that sustainable long-term growth allows firms to achieve higher profitability. These results will be of interest for investors, who should focus on finding companies that can demonstrate annual sales growth for several years. It is also advisable for owners and managers to strive for long-term annual growth in firm sales.